Exploring the Influence of Cognitive Attention on Health Behaviors and Public Health Outcomes Rapidly Developing Socio Cultural Context - Hkyunh, Trueng; Dhang, Phạm; Bui, Le (ScieClouds Publishing, 2023)
This study explores the impact of cognitive attention on public health outcomes in Vietnam, focusing on how cognitive attention influences health-related behaviors such as vaccination adherence, regular health check-ups, medication compliance, and lifestyle habits. Using a structured questionnaire distributed to 30 participants, the research assesses cognitive attention through a modified Cognitive Attention Scale (CAS) and evaluates health behaviors using a Health Behavior Index (HBI). The findings reveal a strong positive correlation between cognitive attention and health behaviors, with higher levels of cognitive attention associated with improved health practices. Multiple regression analysis identified cognitive attention as the strongest predictor of health behaviors, explaining 45% of the variance in health outcomes. Additionally, ANOVA results indicated significant differences in cognitive attention and health behaviors across demographic groups, particularly education level. This study addresses a notable gap in the literature by examining cognitive attention in a non-Western, rapidly developing country context, specifically Vietnam, where socio-cultural factors shape health-related decision-making differently than in Western societies. The research contributes valuable insights into how cognitive attention influences health behaviors and informs public health strategies that can be tailored to the cognitive needs of different demographic groups in Vietnam. The study's findings emphasize the importance of incorporating cognitive factors into public health interventions to improve health outcomes in a culturally relevant manner.